2022
DOI: 10.3389/fbioe.2022.1072942
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-tolerant potential of ordinary Chlorella pyrenoidosa and the promotion of cell harvesting by heterotrophic cultivation at high temperature

Abstract: During the heterotrophic cultivation of microalgae, a cooled process against temperature rise caused by the metabolism of exogenous organic carbon sources greatly increases cultivation cost. Furthermore, microalgae harvesting is also a cost-consuming process. Cell harvesting efficiency is closely related to the characteristics of the algal cells. It may be possible to change cell characteristics through controlling culture conditions to make harvesting easier. In this study, the mesophilic Chlorella pyrenoidos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…A thermal-tolerant species, C. pyrenoidosa, was easily harvested when cultured at 40 • C when compared with culturing at low temperatures. The improvement in harvesting microalgal cells at high temperatures might be ascribed to the increment in cell size and reduction in cell surface charge [87]. One study indicated that an emulsion consisting of cooking oil and cetyltrimethylammonium bromide was utilized for harvesting C. vulgaris.…”
Section: Other Harvesting Methodsmentioning
confidence: 99%
“…A thermal-tolerant species, C. pyrenoidosa, was easily harvested when cultured at 40 • C when compared with culturing at low temperatures. The improvement in harvesting microalgal cells at high temperatures might be ascribed to the increment in cell size and reduction in cell surface charge [87]. One study indicated that an emulsion consisting of cooking oil and cetyltrimethylammonium bromide was utilized for harvesting C. vulgaris.…”
Section: Other Harvesting Methodsmentioning
confidence: 99%